Efeito do ácido zoledrônico na movimentação dentária induzida em ratos - Sousa, Fátima Regina Nunes (2018)
Zoledronic acid (ZA) is a potent bisphosphonate that binds to the hydroxyapatite of the bone surface and acts preferentially in sites of bone formation and resorption, being used in the treatment of bone pathologies. This study aims to evaluate the effects of Zoledronic Acid (ZA) during induced tooth movement (OTM) in rats, in an experimental model that simulates the doses and route of administration of ZA in patients treated with bone metabolic disorders. Wistar rats (180-220 g) divided into two experimental phases were used. In the first phase, different periods of ITM were evaluated (1,4,7,11,14 and 21 days), in order to determine the ideal day to study the effect of ZA. NiTi springs were installed in the first left maxillary molar with 50N allowing the ITM. The maxilla was removed Histological and histometric analyzes of bone and tooth root were performed. On day 21 greater root resorption and tooth displacement were observed, and on day 4, more osteoclasts and necrotic areas were observed when compared to day 0 (p <0.05). In the second phase, four groups were divided: Naive (N), Saline (SAL), Zoledronic Acid with a concentration of 0.2 mg/kg (ZA/0,2) and Zoledronic Acid with a concentration of 1.0 mg /kg/ (ZA/1.0). All groups, except naive, were submitted to NiTi springs installation in the first left maxillary molar with a force of 50g allowing ITM for a period of 4 and 21 days. Administration of ZA (0.2 and 1.0 mg/kg, iv) was performed for 3 consecutive weeks and on day 42, just before the insertion of the springs. These animals were euthanized on days 46 and 63. Jaws were removed for macroscopic and histopathological analyzes (using HE, Picrosirius Red, Mallory), scanning electron microscopy (SEM), computerized microtomography and confocal microscopy. The following parameters were analyzed: bone and root resorption, tooth movement, collagen analysis and blood vessel count. Blood samples were collected for biochemical measurements of alkaline phosphatase, phosphorus and calcium. Treatment with ZA decreased the ITM and the number of osteoclasts and loss of alveolar bone when compared to the naive and saline groups (p <0.05). Treatment with ZA also increased necrotic areas in the periodontal ligament and reduced vascularization (p <0.05). Reduction of radicular resorption was observed in the groups treated with ZA when compared with the saline group. There were no significant changes in the percentage of type I collagen and III between the saline and ZA groups, at any of the concentrations used. In summary, the results of this study show that ZA interferes with ITM and presents anti-resorptive effects on bone and dental tissues associated with decreased of vessel numbers without osteonecrosis. The use of zoledronic acid, therefore, is not a risk factor for the development of maxillary osteonecrosis in the experimental model of ITM used in the present study.